Indonesia’s Energy Transition Norm Diffusion Under the UNFCCC Framework - Dian Khairiani (Eduvest - Journal of Universal Studies, 2025)
The Paris Agreement, adopted by United Nations Framework Convention on Climate Change (UNFCCC) is the starting point for Indonesia's commitment to implementing various energy transition efforts to mitigate global climate change as a transnational crisis. This article analyses the process of energy transition diffusion as a norm that emerged from global discourse to be implemented in Indonesia. Jürgen Rüland's (2018) norm diffusion theory, which provided added values to initial thoughts by other scholars, is used to analyze that the diffusion of energy transition norms in Indonesia is not a linear process but is selective and negotiable, where global norms are modified to conform to national interests and domestic political dynamics. This study finds that Indonesia’s energy transition norm diffusion is constrained by domestic political and socio-economic barriers, including entrenched fossil fuel interests, coal-dependent fiscal structures, electricity price sensitivity, regulatory fragmentation, and uneven institutional capacity. These factors shape a selective adoption process in which global energy transition norms are framed and localized to align with national development priorities rather than fully internalized as transformative commitments. This article argues that Indonesia has not fully adopted the energy transition norm in terms of total transformation, but it tends to be in the localization stage. Through this analysis, hopefully we can identify potential opportunities to accelerate the normative diffusion of energy transition in Indonesia.